COMPARATIVE EVALUATION OF THE FREQUENCY OF RISK FACTORS FOR THE DEVELOPMENT OF CORONARY HEART DISEASE AND ARTERIAL HYPERTENSION IN MINERS WITH ANTHRACOSILICOSIS - Николай Иванович Панев; Наталья Александровна Евсеева (Медицина в Кузбассе, 2022)
The aim of the research was to study the frequency and identify the most significant cardiovascular risk factors in patients with anthracosilicosis in combination with arterial hypertension and coronary heart disease.